Rancang Bangun Sistem Pengajuan Cuti dan Izin Berbasis Website Studi Kasus Unit Kepegawaian PT.XYZ - Arijal, Muhamad; Hermawan, Indra (POLITEKNIK NEGERI JAKARTA, 2021)
The need for increasingly advanced technology covers almost all existing aspects and one of them is within the company, including the personnel department. There are many processes within the staffing department such as employee permits, leave applications that are still done manually and have to interact face-to-face with superiors and HRD and also apply for permits such as overtime, official permits. This activity is still carried out manually and is not effective because too many related parties are involved to obtain permits. Therefore, a system is urgently needed to simplify the process and make the process effective. System development using waterfall which includes system survey, system analysis, system design, system creation, system implementation, and system maintenance which is expected to make it easier for employees to apply for leave, apply for overtime and apply for official permits. This application is based on a website and the creation of this application program uses the waterfall method and uses programming languages ​​such as PHP, javascript and CSS.